Troubled Water in the Eastern Mediterranean. Turkey Challenges Greece and Cyprus Regarding Energy Resources - Axt Heinz-Jürgen (Comparative Southeast European Studies)
The conflict between Turkey on the one hand and Greece and Cyprus on the other was exacerbated when Turkey and Libya reached an agreement on the delimitation of maritime zones to explore and exploit energy resources in late 2019. The countries were on the brink of military confrontation. This was the latest climax of a longer period of conflict and mistrust, during which negative perceptions became more entrenched on all sides. Energy is globally high in demand but exploiting resources in the Mediterranean Sea at competitive prices is difficult. The international community has developed an ambitious Law of the Sea, but its interpretation is controversial. Compromises are needed to de-escalate. What might serve as a ‘bridge over troubled waters’ in the Eastern Mediterranean? The author comments on the available options.